(untitled) (Revista Latino-Americana de Enfermagem, 2019)
Objectives: to identify in the literature the efficacy of serious games to improve knowledge for and/or behavioral changes among overweight or obese children. Method: Systematic Literature Review. The Cochrane Systematic Reviews Handbook was used. The studies were collected from the following databases: Public Medline; Web Of Science; Science Direct; Latin American and Caribbean Health Sciences Literature; and the Health Game Research and Cumulative Index to Nursing & Allied Health Literature. The descriptors were video games and obesity, while the key word was serious games. Inclusion criteria were: studies classified as Randomized Clinical Trials written in English, Spanish or Portuguese and in which children were the subjects of the study. Results: 2,722 studies were identified in the initial search and six studies remained in the final sample. The papers focused on encouraging behavioral changes in players, including physical exercise and improved eating habits. The studies report that serious games are a potential strategy to encourage positive coping with childhood obesity. Conclusion: research in this field is an expanding and promising strategy and serious games represent an alternative means to provide health education to children.